Satellite-derived temperature measures miss key physiologically relevant thermal trends on Palauan reefs - Marilla Lippert; Maurice Goodman; Brendan Cornwell; Katrina Armstrong; Nia S. Walker; Victor Nestor; Yimnang Golbuu; Stephen Palumbi (PLoS ONE, 2026)
Coral reefs are important both economically and culturally to over 1 billion people. However, reefs continue to be threatened by climate change, with some areas now experiencing mass coral bleaching and mortality events due to heat stress on an annual basis. Satellite-derived sea surface temperature data (SSST) are often used as a proxy for in situ temperatures on reefs, and are relied on to identify heat accumulation and assign bleaching risk on reefs worldwide. However, SSST has limitations – readings are only taken at night and on a relatively coarse spatial scale, and multiple studies have exposed discrepancies between SSST and in situ temperatures. In this study, we compare satellite-derived sea surface temperature in Palau to in situ temperature records at 87 reef locations in order to assess how well SSST captures physiologically important thermal trends experienced by corals. We find that while SSST captures average nightly temperatures relatively well, it fails to accurately capture thermal maxima, diurnal range in temperature and heat accumulation measurements like degree heating weeks (DHW) that are relevant in determining coral bleaching risk levels. Though SSST data remain key indicators of temperature stress over global scales, local management of coral reefs, coral restoration, and reef replenishment require more fine scale data in order to accurately understand thermal trends and their implications for coral resilience.